FINANCIAL DIAGNOSTICS OF INTENTIONAL BANKRUPTCY - G. V. Kalvarsky (Real Economics Publishing House, 2014)
The challenges associated with the financial diagnostics of intentional bankruptcy are investigated, suggests ways of their possible solutions are suggested. The official order of diagnostics in the bankruptcy process is critically analyzed. Financial characteristics of intentional bankruptcy are determined, including ones related to with the changes in the financial statements of the debtor. Methodological approaches to the diagnostics of intentional bankruptcy are settled considering its financial mechanism, and the most common financial schemes.